Health Seeking Behaviour During the COVID-19 Pandemic and Influencing Factors in Indonesia - Arif Kurniawan; Elviera Gamelia (Journal of Public Health and Pharmacy, 2025)
Introduction: Data from the Indonesian Ministry of Health on April 13, 2020, indicated that there were up to 4,557 positive COVID-19 cases in 34 provinces, 380 cases that recovered, and 399 cases that died. One of the transmissions of COVID-19 occurs through nosocomial infections that occur in health service institutions, namely hospitals, health centres’, or polyclinics. The significant incidence of nosocomial infection cases in the COVID-19 transmission chain raises the question of whether or not this alters community patterns around health service utilization. The objective of this research was to ascertain the community's health-seeking behavior during the COVID-19 epidemic and the elements that impact that behavior. The novelty of this research focused on the sociocultural context in Indonesia and its contributions to global discussions on pandemic health behavior. Methods: This study used a cross-sectional survey methodology. People living on Indonesian territory make up the research's population. There were 312 participants in the study's sample. Accidental sampling was the method employed for sampling. A questionnaire is the data collection tool and using logistic regression to analysed data. Results: During the COVID-19 pandemic, 56.4 percent of people had good health seeking behavior, compared to 43.6 percent of people who had poor health-seeking behavior. Most of the respondents sought treatment at health services (99.0%), and the rest did not seek treatment at health services (1.0%). Respondents who seek medical treatment include practicing doctors (76.3%), primary health clinics (60.3%), puskesmas (59%), and hospitals (69.2%). During the COVID-19 pandemic, factors that affected health-seeking behavior were income (0.01), marital status (0.001), travel time to health services (0.029), and health-service knowledge (0.069). Conclusion: There is a joint influence of income, marital status, travel time to health services, and knowledge of health seeking behavior during the COVID-19.